Pengaruh Literasi Perbankan Syariah Dan Produk Perbankan Syariah Terhadap Minat Mahasiswa FEBI UIN Sumatera Utara Menabung Di Bank Syariah - Muhammad Rizky Aldiansyah; Muhammad Ridwan; Arnida Wahyuni Lubis (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of Islamic banking literacy and Islamic banking products on the interest of FEBI students at UIN North Sumatra to save in Islamic banks. This research was conducted at the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra with a sample of 68 respondents from the results after conducting the research. Data collection techniques were carried out using a questionnaire, while testing the instruments using validity tests, reliability tests, classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, and multiple linear regression tests. By using purposive sampling technique from calculating multiple linear regression. Based on the results of the analysis, it can be concluded that based on the results of the t test, there is a significant influence of Islamic banking literacy on interest, for the results of the t test of Islamic banking product variables (X2) there is a significant effect of product marketing on interest. Based on the results of the F test (simultaneous) Effect of Islamic Banking Literacy (X1), Islamic Banking Products (X2) have a significant effect on student interest.